COMMUNICATION BETWEEN NURSES AND THE ELDERLY - PRESENT AND FUTURE - Stojanovic, Goran R; Vasiljević Blagojević, Milica; Terzić, Negra; Krstić, Jelena; Vlaisavljević, Željko; Stojanović, Dušan (Annals of Nursing, 2024)
The World Health Organization (WHO) has defined communication quality as one of the five essential skills for a healthy and happy life. Quality communication is particularly important in healthcare, especially for those who have communication difficulties, the majority of whom are elderly individuals. Communication problems among the elderly range from those seeking to prevent the development of communication difficulties to those who already experience challenges such as dysarthria, aphasia, and hearing loss. This study aimed to examine the problems in communication between nurses and the elderly. We searched the PubMed and Embase databases using the keywords: "communication," “adults,” "elderly," and "nurses." The findings suggest that nurses' assistance to the elderly in overcoming communication problems is crucial. It is important to understand the specifics of communication, the basic communication rules with the elderly, and the problems the elderly face in conducting communication adequately. The findings support the idea that nurses can significantly help overcome communication barriers by choosing appropriate strategies, such as repetition, noise elimination, and environmental control, especially in addressing sensory issues. To improve communication between nurses and the elderly, it is necessary to assess all communication barriers, prejudices, beliefs, fears, and the identity of the elderly. Some studies suggest new research topics, revealing that screening to assess sensory functions in the elderly is insufficiently applied and that practical activities within the care of the elderly with sensory impairment are not always utilized. Changing such nursing practices would greatly improve communication and the quality of care for the elderly.
Keywords: communication; elderly; nurses